Selection of kolrabi cabbage varieties and samples for the central zone of Uzbekistan - Amanova Makhfurat; Yakubova Dilafruz; Yakubov Yusuf (E3S Web of Conferences, 2023)
In the Republic of Uzbekistan, experts in the field of vegetable cultivation are faced with the task of satisfying the population's need for vegetable products by not only growing their variety and number but also enhancing their quality. The fact that over 80% of the farmed space was occupied by just ten crops, however, highlights the lack of variety in vegetable production. This is mostly because early-ripening, high-yielding, and vitamin-rich vegetable types appropriate for local circumstances have not been sufficiently developed, and there is a need for more study into gardening methods. For three years 13 varieties and samples of kohlrabi cabbage collection were studied according to morphobiological and economic characteristics. In the course of research, 4 varieties were selected for early ripening, including VIR k-41 (France), Pikant, Nezhenka and Smak (Russia), 4 Giants for productivity, Delikatesnaya belaya, Smak and Violetta varieties were selected, and 4 samples of VIR K-41, Pikant, Smak and Fioletovaya varieties were selected according to their complex characteristics (earliness, productivity and marketability). In the future, these selected varieties and samples will serve as a primary source for the creation of early-early, fruitful, environmental stress-resistant varieties suitable for the climatic conditions of Uzbekistan.